Suppression of charge-density-wave order in TiSe2 studied with high-pressure magnetoresistance. (1st September 2022) - Moulding, Owen; Muramatsu, Takaki; Sayers, Charles J; Da Como, Enrico; Friedemann, Sven
Abstract: TiSe2 undergoes charge density wave (CDW) order which can be suppressed under pressure. We use high-resolution electrical resistivity and magnetoresistance measurements to trace the CDW to the highest pressures of any transport study so far. Comparison with previous work shows that the CDW is very sensitive to pressure conditions resulting in a reduced critical pressure in the presence of non-hydrostaticity. Our analysis indicates that in perfect pressure conditions the intrinsic critical pressure might be as high as 5.6 GPa. At the same time, we observe signatures of enhanced scattering linked to the critical pressure, P CDW . The sensitivity of P CDW to non-hydrostaticity and the enhanced scattering linked to it raises questions of how the superconductivity induced in TiSe2 under pressure is related to the CDW order.